2010
DOI: 10.1111/j.1749-6632.2010.05745.x
|View full text |Cite
|
Sign up to set email alerts
|

A role for calreticulin in the pathogenesis of rheumatoid arthritis

Abstract: Calreticulin (CRT) plays a role in the clearance of dying cells and has been implicated in autoimmunity. Recent evidence indicates that cell surface CRT (csCRT) acts as a signal transducing receptor for the rheumatoid arthritis (RA) shared epitope (SE). The SE binding site on CRT has been mapped to amino acid residues 217-223 in the P-domain. Upon interaction with dendritic cells (DCs), the SE activates potent immune regulatory events. In CD8α + DCs, which express higher abundance of csCRT, the SE inhibits the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 75 publications
(129 reference statements)
3
25
0
Order By: Relevance
“…In mammals where the bulk of data has been collected, CRT has been linked to both intracellular and extracellular functions, in health and disease (Holoshitz et al, 2010, Martins et al, 2010, Gold et al, 2010, Wang et al, 2012). The role of CRT in intracellular Ca 2+ homeostasis associates this protein with multiple functions including heart muscle function, adipocyte differentiation and cellular stress responses (Tarr et al, 2010, Van Duyn Graham et al, 2010 Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In mammals where the bulk of data has been collected, CRT has been linked to both intracellular and extracellular functions, in health and disease (Holoshitz et al, 2010, Martins et al, 2010, Gold et al, 2010, Wang et al, 2012). The role of CRT in intracellular Ca 2+ homeostasis associates this protein with multiple functions including heart muscle function, adipocyte differentiation and cellular stress responses (Tarr et al, 2010, Van Duyn Graham et al, 2010 Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…14 We have recently identified the SE as a ligand that binds to cell surface calreticulin and activates pro-osteoclastogenic signalling. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] Using cell-free synthetic ligands expressing the SE motif, we have demonstrated that the SE enhanced Th17 polarisation 24 and directly activated OC differentiation. 26 When administered in vivo to mice with collagen-induced arthritis, the SE ligand enhanced joint inflammation, increased the abundance of tissue and bone marrow OCs, and enhanced bone damage in arthritic joints.…”
Section: Key Questionsmentioning
confidence: 92%
“…Calreticulin, despite the lack of a classic secretion peptide or transmembrane domain, plays a role in the clearance of dying cells and has been implicated in autoimmunity. Recent evidence indicates that cell surface calreticulin acts as a signal transducing receptor for the rheumatoid arthritis (RA)-shared epitope (SE) (Holoshitz et al, 2010). However, the biological function of calreticulin and nucleolin in anti-b2GPI antibodies-induced EC activation is not clear.…”
Section: Tlr4 and Apl-induced Cell Activation: In Vitro Studiesmentioning
confidence: 98%